Using Social Media to Reduce Language Barrier among Foreign Students in Pakistan - Taha Shabbir; Syed Minhaj Hussain; Sabir Ahmed; Arjumand Zehra; Ahmar Hamid Khan (Program Pascasarjana Universitas Negeri Makassar, 2021)
Social networking is rapidly changing the communication environment of contemporary social media. Social media's growth has had a profound effect on students' academic lives. Institutions and researchers are actively playing with social networking technologies with the expectation of stimulating strategic thinking, collaboration, and knowledge rising. Today's higher education establishments have adopted social media to communicate for students with teachers, fellow students, and other higher authorities. This necessitated the investigation and analysis of the impact of social media on students' academic lives in this report. The study argued for a qualitative approach to assessing these effects. Thirty international students enrolled at Karachi's university were randomly chosen and questioned over four weeks. Following an examination of the phenomena that motivated the study and transcription of the participants' comments, the results suggest that students in higher education often use social networking and that participants believe that social media plays a major role in their academic success. Social networking applications can augment classroom content and have a beneficial effect on conversations, community service, and authoring. However, since these media are inherently accessible, it is critical to closely understand the advantages, consequences, and pitfalls of transparency, as well as the critical nature of ongoing contact with students in order to discuss their concerns and resolve any problems that arise as a result of social media use. The analysis concludes that as an international student studying in Pakistan, social media contributes to academic creativity.